Biomass Estimation of Dry Tropical Woody Species at Juvenile Stage - R. K. Chaturvedi; A. S. Raghubanshi; J. S. Singh (The Scientific World Journal)
Accurate characterization of biomass in different forest components is important to estimate their contribution to total carbon stock. Due to lack of allometric equations for biomass estimation of woody species at juvenile stage, the carbon stored in this forest component is ignored. We harvested 47 woody species at juvenile stage in a dry tropical forest and developed regression models for the estimation of above-ground biomass (AGB). The models including wood-specific gravity (𝜌) exhibited higher 𝑅2 than those without 𝜌. The model consisting of 𝜌, stem diameter (𝐷), and height (𝐻) not only exhibited the highest 𝑅2 value but also had the lowest standard error of estimate. We suggest that 𝜌-based regression model is a viable option for nondestructive estimation of biomass of forest trees at juvenile stage.